2019
DOI: 10.37190/abb-01435-2019-03
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and dynamic changes in plantar pressure distribution, as well as in posture during slow walking in flat and high-heel shoes

Abstract: The aim of the study was to assess the differences in plantar pressure distribution and in posture during slow and very slow walking on the treadmill in flat and high-heeled shoes. Methods: The Pedar-X ® (Novel, Munich, Germany) measuring insoles were used to measure the plantar pressure distribution and to assess temporal parameters during walking on the treadmill with the speed v 1 = 0.97 ms-1 and v 2 = 0.56 ms-1 in flat shoes (FS) and HH. For postural measurement, the SonoSens Monitor Analyzer (Gefremed, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
2
4
1
Order By: Relevance
“…Therefore, the increased plantarflexion of the ankle leads to reduced pronation during support with HHS, and part of the shock absorbing function of pronation may be lost, resulting in greater peak vertical GRF [15]. Peak pressure, maximum force and contact area are significantly higher in the forefoot than in the midfoot and rearfoot when walking in HHS compared with walking in flat shoes or barefoot, supporting previous studies [64,[76][77][78]. This finding suggests that HHS triggers a weight transfer mechanism that shifts plantar pressure to the forefoot, possibly due to the elevation of the heel causes a distinct anterior displacement of the COG of the body and reduces the cushioning effect of the arch [15,64,79].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, the increased plantarflexion of the ankle leads to reduced pronation during support with HHS, and part of the shock absorbing function of pronation may be lost, resulting in greater peak vertical GRF [15]. Peak pressure, maximum force and contact area are significantly higher in the forefoot than in the midfoot and rearfoot when walking in HHS compared with walking in flat shoes or barefoot, supporting previous studies [64,[76][77][78]. This finding suggests that HHS triggers a weight transfer mechanism that shifts plantar pressure to the forefoot, possibly due to the elevation of the heel causes a distinct anterior displacement of the COG of the body and reduces the cushioning effect of the arch [15,64,79].…”
Section: Discussionsupporting
confidence: 81%
“…The instability caused by HHS ultimately leads to a significant reduction in walking speed [10]. The findings on step frequency are inconsistent, with no significant differences in step frequency in our study, possibly because the preferred walking speed of the participants had a large variation and part of the study was conducted on a treadmill at a fixed speed, whereas previous studies showed that walking at different speeds with HHS produces different walking characteristics [8,64,65]. In the funnel plot, the step length and step width showed a significant asymmetry, which indicates a large bias, therefore, the overall results need to be treated with caution.…”
Section: Discussioncontrasting
confidence: 78%
“…Severe scoliosis cases might have shorter body height due to the presence of larger curvatures; however, no such differences were observed, probably due to the small sample size of severe cases. Many previous studies have reported that plantar pressure and gait are affected by several factors such as age, sex, BMI, and walking speed [ 37 39 ]. Therefore, plantar pressure distribution and gait in adolescents with mild, moderate, and severe scoliosis were analyzed and compared with matched healthy peers, while considering age, sex, BMI, and walking speed as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…It is part of the equipment, homogeneously distributed resistive sensors, with resolution depending on the size of the platform, approximately one sensor/cm 2 . 28 The adolescents walked at a pre-selected cadence to ensure they had reached the same speed. All went through a phase of adaptation to the established speed to get the adolescents used to the collection environment and the instruments, so there would be a decrease in the backlash.…”
Section: Biomechanical Assessment Of Gait: Plantar Pressure Distributionmentioning
confidence: 99%
“…Thus, the foot was divided into three major areas: hindfoot (30% of foot length), midfoot (30% of foot length), and forefoot and toes (40% of foot length). 28…”
Section: Biomechanical Assessment Of Gait: Plantar Pressure Distributionmentioning
confidence: 99%